Praktik Pendidikan Inklusif untuk Anak Berkebutuhan Khusus di Sekolah Dasar - Atika, Atika (Center for Gender and Children Studies, Lembaga Penelitian dan Pengabdian Masyarakat (LP2M) UIN Sultan Thaha Saifuddin Jambi, 2024)
This study aims to examine the practice of inclusive education for children with special needs in elementary schools. The study identified several key challenges, including a lack of curriculum flexibility, teacher readiness and competence, support from parents and the community, and limited infrastructure and resources. Through interviews and observations, it was found that the existing curriculum is often inadequate to accommodate the needs of students with special needs. In addition, many teachers feel less confident in teaching children with special needs due to the lack of training. Parental and community support also plays an important role, but stigma and lack of understanding are still obstacles. Inadequate infrastructure and resources further hinder the implementation of inclusive education. This research emphasizes the importance of adaptive policies, continuous training for teachers, community education, and improving infrastructure and resources to create an inclusive learning environment.